Reading Trauma in Antonia White’s Confessional Autobiographical Novels - Ibrahim, Juan Abdullah (Al-Adab Journal, 2022)
White presents a clear picture of a woman who suffers from a traumatic psychological state. During her childhood, she was continuously raped by her father. Such kind of anxiety and irritation White reveals in a series of her autobiographical writings. Due to Psychiatrists, it is a valid view that a significant part of White’s mental breakdown is due to her unconscious sense of anxiety, which goes back to her childhood period. Psychoanalytic theories of Freud and Cathy Caruth are used to justify most of the odd situations White presents in her novels. The study aims at describing such anxiety in Antonia White’s Quartet stories. It discusses the psychoanalytic theories of Freud and Caruth’s post-traumatic stress disorder, PTSD. In spite of being humiliated, sexually abused and treated badly, White aimed at creating a unified female self in her autobiographical novels. She has done so through her daring style and rebelling against the patriarchal system by suppressing her anxiety in writing.